The Indonesian version of Individual Work Performance Questionnaire (IWPQ): Structure factor and criterion validity - Widyastuti, Tria; Ramdani, Zulmi; Alim, Syahrul; Harlianty, Rully Afrita (Faculty of Psychology, Universitas Negeri Yogyakarta, 2024)
The aims of this study are to examine the structure factor of Indonesian version of Individual Work Performance Questionnaire (IWPQ) and to test the construct of IWPQ by correlating with Utrecht Work Engagement Scale (UWES) as criterion. A total of 609 data from employees across Indonesia were involved in the research (Study 1 = 231, and Study 2 = 378). Data analysis was done using CFA to test the evidence validity based on internal structure and Pearson correlation to examine evidence of validity based on relation to other variables. This study confirmed the three-factor model of IWPQ in study 1 and study 2 with independent samples. The Indonesian version of the IWPQ also correlate positively with work engagement as criterion proving the evidence validity based on relation to others variable. The finding of this research strengthens the Indonesian version of IWPQ as a good tool in measuring work performance